Sustainability of the currency board in Bosnia and Herzegovina in the conditions of a negative interest rate on the reserve currency - Rajko Tomaš (Journal of Central Banking Theory and Practice, 2023)
The Currency Board in Bosnia and Herzegovina (BiH) uses the euro as a reserve currency in the conditions of a negative nominal interest rate on deposits with the ECB. In this paper, we investigated the impact of negative interest rates on deposits and negative yields on bonds denominated in euro on the general advantages of the currency board and the consequences for the functioning of the currency board in BiH. The impact of negative interest rates was measured by the currency board coverage index (IC). A negative nominal interest rate on the reserve currency creates a negative seigniorage in the country of the currency board, increases the costs of issuing domestic money and reduces the competitiveness of the economy. The monetary policy of the ECB in the conditions of the COVID-19 crisis generates negative influences on the functioning of the currency board. The COVID-19 crisis poses a threat to currency board coverage in BiH. Technically, a currency board can also function in terms of negative interest on the invested reserve currency as long as it can cover the costs of its business.
Keywords: E42; E49; E50; 330; currency board; negative nominal interest rate; currency board coverage index; reserve currency; seigniorage